Laser Capture Microdissection of Pancreatic Acinar Cells to Identify Proteomic Alterations in a Murine Model of Caerulein‐Induced Pancreatitis. Issue 4 (April 2017) - Shapiro, John P; Komar, Hannah M; Hancioglu, Baris; Yu, Lianbo; Jin, Ming; Ogata, Yuko; Hart, Phil A; Cruz‐Monserrate, Zobeida; Lesinski, Gregory B; Conwell, Darwin L
Abstract : OBJECTIVES: : Chronic pancreatitis (CP) is characterized by inflammation and fibrosis of the pancreas, leading to pain, parenchymal damage, and loss of exocrine and endocrine function. There are currently no curative therapies; diagnosis remains difficult and aspects of pathogenesis remain unclear. Thus, there is a need to identify novel biomarkers to improve diagnosis and understand pathophysiology. We hypothesize that pancreatic acinar regions contain proteomic signatures relevant to disease processes, including secreted proteins that could be detected in biofluids. METHODS: : Acini from pancreata of mice injected with or without caerulein were collected using laser capture microdissection followed by mass spectrometry analysis. This protocol enabled high‐throughput analysis that captured altered protein expression throughout the stages of CP. RESULTS: : Over 2, 900 proteins were identified, whereas 331 were significantly changed ≥2‐fold by mass spectrometry spectral count analysis. Consistent with pathogenesis, we observed increases in proteins related to fibrosis (e.g., collagen, P <0.001), several proteases (e.g., trypsin 1, P <0.001), and altered expression of proteins associated with diminished pancreas function (e.g., lipase, amylase, P <0.05). In comparison with proteomic data from a public data set of CP patients, a significant correlation was observed between proteomic changes in tissue from both the caerulein model and CP patients ( r =0.725, P <0.001). CONCLUSIONS: : This study illustrates the ability to characterize proteome changes of acinar cells isolated from pancreata of caerulein‐treated mice and demonstrates a relationship between signatures from murine and human CP.